ANALISIS KESALAHAN FONOLOGIS DALAM KETERAMPILAN MEMBACA TEKS BAHASA ARAB - Lathifah, Fitria; Syihabuddin, Syihabuddin; Al Farisi, M. Zaka (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This research aimed to analyze the phonological errors made by the students of Arabic department when processing of learning activity about reading skill. The research design used in this research was content analysis. The data collection method used was listening method with free listening-speaking technique, writting technique and recording technique. The result of this research showed up that the students’ phonological errors that often occured were on fricative sound such as (حذصظش خ and ف) whereas for the explosion sound was on ض ط and ق. Among of those errors, the most difficult and the biggest errors were ع and ض.